"Best practice" for extracorporeal photopheresis in acute and chronic graft‐versus‐host disease by Societa' Italiana di Emaferesi and Manipolazione Cellulare and Gruppo Italiano Trapianto Midollo Osseo: a national survey to ascertain its degree of application in Italian transplant centers. Issue 1 (13th November 2017) - Pierelli, Luca; Bosi, Alberto; Olivieri, Attilio
Abstract : BACKGROUND: A recent "best practice" promoted and published by Gruppo Italiano Trapianto Midollo Osseo (GITMO) and Societa' Italiana di Emaferesi and Manipolazione Cellulare (SIDEM) on the use of extracorporeal photopheresis (ECP) in acute and chronic graft‐versus‐host disease (GVHD) has been tested for the degree of agreement and application among Italian transplant centers. STUDY DESIGN AND METHODS: Twenty‐four Italian centers coordinating a pair number of transplant programs completed the Web‐based survey within the fixed deadline, representing approximately 52% of those centers that have a GITMO‐accredited allogeneic transplant program that routinely uses ECP in GVHD. RESULTS: The level of full agreement was more than 85% for most of the answers given by the best practice (14 of 16) to the various issues. For the answers of two questions dealing with indications of ECP in acute GVHD and with safety and quality measures we observed a full agreement of 62 and 50%, respectively. CONCLUSION: This report shows a very good success of best practice among Italian centers, indicating that, after 3 years, it seems to be still updated and useful. More discussion has been observed for safety and quality measures and, likely, this issue deserves a dedicated focus on a future consensus report.